Gender Representation and Educational Equity: A Critical Analysis of Indonesian Senior High School English Textbooks - Hia, Nadia Virdhani; Rangkuti, Rahmadsyah; Sinar, T. Silvana; Zein, T. Thyrhaya; Fithriani, Rahmah (Universitas Hamzanwadi, 2025)
Despite increasing global awareness of gender equity, research on how English textbooks shape students’ perceptions of gender remains limited in Indonesia. This study examines the linguistic and visual gender portrayals in two government-issued English textbooks for Grade X and XI senior high school students (revised 2017 editions), which are widely used nationwide. Using a qualitative content analysis integrated with critical discourse analysis, the study systematically analyzed all textual and visual elements, including dialogues, narratives, exercises, and illustrations, guided by established frameworks for evaluating gender representation. Quantitative coding documented frequency and types of gender representation, while discursive interpretation examined how language and images construct social meanings. Findings reveal 404 textual and 201 visual gender representations: although textual mentions in Grade X show near parity (35% male; 35% female), Grade XI reflects male predominance (43.5% vs. 33.5%), and visuals overall favor male visibility (43.7%). Female figures are disproportionately associated with domesticity, emotional expression, and limited occupations, whereas males appear in more diverse, agentive, and authoritative roles. Gendered language reinforces these patterns through masculine generics and adjectives emphasizing appearance for females and intellect for males. These findings suggest that while attempts at balance exist, textbooks continue to reproduce traditional gender ideologies. The study contributes a nuanced understanding of how school materials reflect and shape sociocultural norms and offers implications for textbook design and educational policy to foster inclusive and equitable gender representation aligned with SDG 5.